2018
DOI: 10.1371/journal.pone.0206093
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection modulates the metabolomic profile of microglial cells

Abstract: Zika virus (ZIKV) is an emerging arbovirus of the Flaviviridae family. Although infection with ZIKV generally leads to mild disease, its recent emergence in the Americas has been associated with an increase in the development of the Guillain-Barré syndrome in adults, as well as with neurological complications, in particular congenital microcephaly, in new-borns. To date, little information is available on neuroinflammation induced by ZIKV, notably in microglial cells in the context of their metabolic activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…Analysis of differential expressed circRNAs has revealed changes in the metabolism of fatty acids upon BmCPV infection ( Hu et al, 2018 ).All these reports have demonstrated that lipid-related metabolisms play vital roles in the life cycles of RNA viruses. It is worth noting that the virus-induced changes of cellular metabolic activity generally facilitate the progress of virus infection ( Diop et al, 2018 ; Tian et al, 2019 ). To date, the lipid metabolism in cells infected by double-stranded RNA (dsRNA) viruses, such as, BmCPV remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of differential expressed circRNAs has revealed changes in the metabolism of fatty acids upon BmCPV infection ( Hu et al, 2018 ).All these reports have demonstrated that lipid-related metabolisms play vital roles in the life cycles of RNA viruses. It is worth noting that the virus-induced changes of cellular metabolic activity generally facilitate the progress of virus infection ( Diop et al, 2018 ; Tian et al, 2019 ). To date, the lipid metabolism in cells infected by double-stranded RNA (dsRNA) viruses, such as, BmCPV remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, hyperactivation of microglia induces chronic inflammation and neurodegeneration [ 30 ]. ZIKV-infected microglia exhibit an activated phenotype, characterized by the upregulation of several inflammatory cytokines and may also transmit the virus to other target cells in the brain [ 9 , 31 ]. To determine the role of IL-22 in the microglial profile during ZIKV infection, we analyzed the microglial phenotype in both WT and IL-22 -/- neonatal mice.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA levels of IFN-γ , as well as its inducible chemokines, CXCL9 and CXCL10 , were not changed significantly. However, the level of brain TNF-α , which is the main cytokine produced by microglia [ 31 , 32 ], was significantly decreased in IL-22 -/- mice (Fig. S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA levels of IFN-γ, as well as its inducible chemokines, CXCL9 and CXCL10, were not changed signi cantly. However, the level of brain TNF-α, which is the main cytokine produced by microglia [27,28], was signi cantly decreased in IL-22 −/− mice (Fig. S3).…”
Section: Il-22 De Ciency Reduced Microglia Activation In Zikvinfectedmentioning
confidence: 98%
“…However hyperactivation of microglia induces chronic in ammation and neurodegeneration [26]. ZIKV-infected microglia exhibit an activated phenotype, characterized by upregulation of several in ammatory cytokines and may also transmit virus to other target cells in the brain [9,27]. To determine the role of IL-22 in microglial pro le during ZIKV infection, we analyzed the microglial phenotype in both IL-22 −/− and WT neonatal mice.…”
Section: Il-22 De Ciency Reduced Microglia Activation In Zikvinfectedmentioning
confidence: 99%